Clinical progression is associated with poor prognosis whatever the treatment line in metastatic castration resistant prostate cancer: The CATS international database. (January 2020) - Delanoy, Nicolas; Hardy-Bessard, Anne-Claire; Efstathiou, Eleni; Le Moulec, Sylvestre; Basso, Umberto; Birtle, Alison; Thomson, Alastair; Krainer, Michael; Guillot, Aline; De Giorgi, Ugo; Hasbini, Ali; Daugaard, Gedske; et al.
Abstract: Aim of the study: Our goal was to evaluate the impact of progression type (prostate-specific antigen [PSA] only, radiological or clinical) at initiation of first-, second- and third life-extending therapy (LET) on treatment outcomes in metastatic castration-resistant prostate cancer (mCRPC) patients, by performing a post-hoc analysis using data from the CATS international registry. Methods: The 669 consecutive mCRPC patients of the CATS registry were classified according to their type of progression at initiation of each LET: PSA only (PSA-p), radiological (±PSA) (Radio-p); or clinical (±PSA, ±radiological) progression (Clin-p). Overall survival (OS), the primary endpoint, was calculated from initiation of the first-, second- and third-LET to death for each sequence. Results: Median OS was shorter in the Clin-p group compared with the PSA-p group (14-month difference in first line; around 7-month difference in second- and third line). Shorter progression-free survival (PFS) was also observed in Clin-p patients, whatever the treatment is. Clinical progression seemed to be associated with a shorter duration of therapy with androgen receptor-targeted therapy (ART) compared with taxanes. Conclusions: Clinical progression at initiation of a LET is associated with poor outcomes including shorter PFS and OS as well as clinical and biological features of aggressive disease. Stratifying patients in clinical trials according to disease progression type may prevent selection bias and data heterogeneity. In daily practice, first signs of clinical progression may prompt physicians to consider starting a new LET, independently of PSA levels. Highlights: Metastatic castration-resistant prostate cancer (mCRPC) is treated by using several drugs. Prognostic factors are useful to determine optimal treatment sequences in mCRPC. Data were collected in 661 real-life patients over three successive treatment lines. Post-hoc analysis showed that clinical progression was associated with poor outcomes. Type of disease progression at the start of each line is a useful prognostic factor.